The Grace Dieu experience of the Anglican church - Mokwele, Alfred Percy Phuti (My University, 1988)
Refer to the document
Thesis (M. Ed.) -- University of the North, 1988
Keywords: Anglican church; Black education; Mission schools; Dissertations, Academic -- Education; Education -- Blacks -- South Africa -- History; Grace Dieu mission school -- Transvaal -- History; Missions -- South Africa -- Transvaal